Identifying Risk-based Selection in Social Insurance: New Approaches and Findings - Mette Ejrnæs; Stefan Hochguertel (Tinbergen Institute, 2022)
We study risk-based selection into a voluntary unemployment insurance (UI) scheme. To disentangle behavioral effects from selection, we exploit variation in the sign-up induced by an early retirement scheme embedded into the UI system. We combine an event study with a difference-in-difference approach applied to Danish register data to quantify the selection. We find that individuals who sign up for UI are negatively selected in terms of subsequent unemployment. However, we find important heterogeneity across education and gender. In addition, life cycle events (such as buying a first home) point to effects consistent with dynamic selection on moral hazard.
Keywords: J64; D82; J65; 330; Unemployment; insurance; selection